2012
DOI: 10.1371/journal.pone.0034866
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Distribution of Psychiatric Births in England

Abstract: There is general consensus that season of birth influences the risk of developing psychiatric conditions later in life. We aimed to investigate whether the risk of schizophrenia (SC), bipolar affective disorder (BAD) and recurrent depressive disorder (RDD) is influenced by month of birth in England to a similar extent as other countries using the largest cohort of English patients collected to date (n=57,971). When cases were compared to the general English population (n=29,183,034) all diseases showed a seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…and early spring births in psychometric schizotypy can only be given with caution. As was already suggested for the seasonal distribution of psychiatric births, peaks may correlate with cyclic meteorological and environmental factors such as extreme temperatures, vitamin D or nutritional deficiency and variation in maternal hormones (Castrogiovanni et al, 1998;Disanto et al, 2012;Tochigi et al, 2004). However, viral infection is one variable that has been most extensively studied with regard to the seasonal effect on schizophrenia (Tochigi et al, 2004) and is also discussed in relation to schizotypy by previous studies (Bolinskey et al, 2013;Cohen and Najolia, 2011;Córdova-Palomera et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…and early spring births in psychometric schizotypy can only be given with caution. As was already suggested for the seasonal distribution of psychiatric births, peaks may correlate with cyclic meteorological and environmental factors such as extreme temperatures, vitamin D or nutritional deficiency and variation in maternal hormones (Castrogiovanni et al, 1998;Disanto et al, 2012;Tochigi et al, 2004). However, viral infection is one variable that has been most extensively studied with regard to the seasonal effect on schizophrenia (Tochigi et al, 2004) and is also discussed in relation to schizotypy by previous studies (Bolinskey et al, 2013;Cohen and Najolia, 2011;Córdova-Palomera et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…The causative factors between SOB and psychiatric conditions are still unknown, but one must ask if it is really a heightened risk in certain months that contributes to the effects of SOB and other diseases or if it is not better to speak of seasonal distribution (Disanto et al, 2012). Season has immense influences on the global environment, climate, sunlight and infection (Disanto et al, 2012), so it seems likely that it also influences the human immune system and its proneness to infection and physical or psychiatric diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s and 1980s, more than 200 studies were published on schizophrenia and other diseases of the mental and nervous system. Most of these studies found that the season of birth influences the risk of developing psychiatric conditions later in life (Disanto et al 2012). Eysenck took up the topic of the impact of month of birth on life span in his book "Astrology.…”
Section: Month Of Birthmentioning
confidence: 99%
“…Season of birth (SOB) has been shown to modify risk for several health outcomes, including a number of neuropsychiatric disorders (Brewerton, Dansky, O'Neil, & Kilpatrick, 2012;Cheng et al, 2013;Davies, Welham, Chant, Torrey, & McGrath, 2003;Disanto et al, 2012;Dome, Kapitany, Ignits, & Rihmer, 2010). In effect, there is evidence indicating that seasonality influences fetal growth and development (Currie & Schwandt, 2013;Flouris, Spiropoulos, Sakellariou, & Koutedakis, 2009;Strand, Barnett, & Tong, 2011;Watson & McDonald, 2007), which bears significance for psychiatric research.…”
Section: Introductionmentioning
confidence: 99%